Chemogenetic Inhibition Reveals That Processing Relative But Not Absolute Threat Requires Basal Amygdala - Campese, Vincent D. (J Neurosci, 2019)
While our understanding of appetitive motivation has benefited immensely from the use of selective outcome devaluation tools, the same cannot be said about aversive motivation. Findings from appetitive conditioning studies have shown that basal amygdala is required for behaviors that are sensitive to updates in outcome value, but similar results in aversive motivation are difficult to interpret due to a lack of outcome specificity. The studies reported here sought to develop procedures to isolate sensory-specific processes in aversive learning and behavior and to assess the possible contribution of the basal amygdala. Post-training changes to outcome value produced commensurate changes to subsequently tested conditioned responding in male rodents. Specifically, increases in shock intensity (i.e., inflation) augmented, while repeated exposure to (i.e., habituation of) an aversive sound (klaxon-horn) reduced freezing to conditioned stimuli previously paired with these outcomes. This was extended to a discriminative procedure, in which following revaluation of one event, but not the other, responding was found to be dependent on outcome value signaled by each cue. Chemogenetic inactivation of basal amygdala impaired this discrimination between stimuli signaling differently valued outcomes, but did not affect the revaluation process itself. These findings demonstrate a contribution of the basal amygdala to aversive outcome-dependent motivational processes. SIGNIFICANCE STATEMENT The specific content of pavlovian associative learning has been well studied in appetitive motivation, where the value of different foods can be easily manipulated. This has facilitated our understanding of the neural circuits that generate different forms of motivation (i.e., sensory specific vs general). Studies of aversive learning have not produced the same degree of understanding with regard to sensory specificity due to a lack of tools for evaluating sensory-specific processes. Here we use a variant of outcome devaluation procedures with aversive stimuli to study the role of basal amygdala in discriminating between aversive stimuli conveying different degrees of threat. These findings have implications for how we study generalized threat to identify dysregulation that can contribute to generalized anxiety.